Characterization of Octa-aminopropyl polyhedral oligomeric silsesquioxanes (OA-POSS) nanoparticles and their effect on sweet basil (Ocimum basilicum L.) response to salinity stress - Gohari, Gholamreza; Panahirad, Sima; Mohammadi, Asghar; Kulak, Muhittin; Dadpour, Mohamad Reza; Lighvan, Zohreh Mehri; Sharifi, Sina; Eftekhari-Sis, Bagher; Szafert, Sławomir; Fotopoulos, Vasileios; Akbari, Ali (My University, 2023)
Salt stress is of the most detrimental abiotic stress factors on either crop or non-crop species. Of the strategies employed to boost the performance of the plants against harmful impacts of salt stress; application of novel nano-engineered particles have recently gained great attention as a promising tool. Octa-aminopropyl polyhedral oligomeric silsesquioxanes nanoparticles (OA-POSS NPs) were synthesized and then a foliar-application of OA-POSS NPs were carried out on sweet basil plants subjected to the salt stress. In that context, interactive effects of OA-POSS NPs (25, 50 and 100 mg L-1) and salinity stress (50 and 100 mM NaCl) were assayed by estimating a series of agronomic, physiological, biochemical and analytical parameters. OA-POSS NPs decreased the harmful effects of salinity by increasing photosynthetic pigment content, adjusting chlorophyll fluorescence, and triggering non-enzymatic (phenolic content) and enzymatic antioxidant components. The findings suggested that 25 mg L-1 OA-POSS NPs is the optimum concentration for sweet basil grown under salt stress. Considering the essential oil profile, estragole was the predominant compound with a percentage higher than 50% depending on the treatment. In comparison to the control group, 50 mM NaCl did not significantly affect estragole content, whilst 100 mM NaCl caused a substantial increase in estragole content. Regarding OA-POSS NPs treatments, increments by 16.8%, 11.8% and 17.5% were observed following application with 25, 50 and 100 mg L-1, respectively. Taken together, the current study provides evidence that POSS NPs can be employed as novel, 'green' growth promoting agents in combating salt stress in sweet basil.
Keywords: Abiotic stress; Essential oil; Nanotechnology; Polyhedral oligomeric silsesquioxanes (POSS); Reactive oxygen species